Microscopy and spatial-metabolomics identify tissue-specific metabolic pathways uncovering salinity and drought tolerance mechanisms in Avicennia marina and Phoenix dactylifera roots - Paula Oyarce; Ting Ting Xiao; Corinna Henkel; Signe Frost Frederiksen; Jose Kenyi Gonzalez-Kise; Wouter Smet; Jian You Wang; Salim Al-Babili; Ikram Blilou (Scientific Reports)
Abstract In arid and semi-arid climates, native plants have developed unique strategies to survive challenging conditions. These adaptations often rely on molecular pathways that shape plant architecture to enhance their resilience. Date palms (Phoenix dactylifera) and mangroves (Avicennia marina) endure extreme heat and high salinity, yet the metabolic pathways underlying this resilience remain underexplored. Here, we integrate tissue imaging with spatial metabolomics to uncover shared and distinct adaptive features in these species. We found that mangrove roots accumulate suberin and lignin in meristematic tissues, this is unlike other plant species, where only the differentiation zones contain these compounds. Our metabolomic analysis shows that date palm roots are enriched in metabolites involved in amino acid biosynthesis, whereas compounds involved in lignin and suberin production were more abundant in mangrove roots. Matrix-assisted laser desorption/ionization mass spectrometry imaging (MALDI-MSI) revealed tissue- and species-specific metabolite distributions in root tissues. We identified common osmoprotectants accumulating in the exodermis/epidermis of date palm and mangrove root meristems, along with a unique metabolite highly abundant in the inner cortex of date palm roots. These findings provide valuable insights into stress adaptation pathways and highlight key tissue types involved in root stress response.